2017
DOI: 10.1016/j.omtm.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication of Bone Morphogenetic Protein-2 Gene-Activated Porous Poly-L-Lactide Scaffold for Bone Induction

Abstract: Bone morphogenetic protein 2 (BMP2) is an efficacious inducer for the osteogenesis of mesenchymal stem cells (MSCs). Conventional applications of BMP2 have involved either the direct incorporation of BMP2 protein or ex vivo BMP2 gene transfer into stem cells prior to their transplantation. These approaches are able to promote bone formation to some extent; however, they are hampered by either the lack of stability and sustainability of BMP2 protein or the time-consuming and cost-prohibitive in vitro cell cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The hBMSCs were isolated as previously described 11,14,16,17 and cultured in proliferation medium (PM) (GM; α‐MEM +1% Antibiotic‐Antimycotic +10% fetal bovine serum [FBS]; Gibco/Life Technologies, Grand Island, New York) and 1 ng/mL Fibroblast Growth Factor 2 (FGF‐2, R&D Systems, Minneapolis, Minnesota), the hBMSCs were then plated into T150 tissue culture flasks and cultured in 37°C with 5% CO 2 . The nonadherent cells were washed by phosphate‐buffered saline after 3 days culture, and GM were changed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The hBMSCs were isolated as previously described 11,14,16,17 and cultured in proliferation medium (PM) (GM; α‐MEM +1% Antibiotic‐Antimycotic +10% fetal bovine serum [FBS]; Gibco/Life Technologies, Grand Island, New York) and 1 ng/mL Fibroblast Growth Factor 2 (FGF‐2, R&D Systems, Minneapolis, Minnesota), the hBMSCs were then plated into T150 tissue culture flasks and cultured in 37°C with 5% CO 2 . The nonadherent cells were washed by phosphate‐buffered saline after 3 days culture, and GM were changed every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…The primer sequences for osteocalcin (OCN) and alkaline phosphatase (ALP) were as follows: forward, 5′‐TGACGAGTTGGCTGACCA‐3′ and reverse, 5′‐AGGGTGCCTGGAGAGGAG‐3′; forward, 5′‐GACCTCCTCGGAAGACACTC‐3′ and reverse, 5′‐TGAAGGGCTTCTTGTCTGTG‐3′, respectively. The results were analyzed using the comparative CT method according to our published protocol 14 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone morphogenetic protein‐2 (BMP2)‐expressing AAV2 has also been coated onto hydroxyapatite in a similar fashion and demonstrated to induce bone formation in a rat model (Nasu et al, ). More recently, a group generated poly( l ‐lactic acid) scaffolds incorporating AAV encoding BMP2 and evaluated the osteogenic potential in vitro and in vivo with seeded human mesenchymal stem cells (hMSCs) (Xue et al, ). Despite encouraging outcomes seen from the aforementioned examples, some studies have also reported low transduction efficiencies.…”
Section: Introductionmentioning
confidence: 99%